ANALYSIS OF THE STATE OF DEVELOPMENT OF INNOVATIVE ACTIVITY IN THE TEXTILE INDUSTRY - Davranov Orzu Abdujabborovich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
In today's world, in the context of globalization and integration of the national economy into the world community, it is difficult to overestimate the role of innovation. Today, innovations surround us everywhere, both in the economic and social spheres. In the age of accelerated development of information and communication technologies, large industrial enterprises and small businesses need to respond quickly to changing national and global needs.